Heat acclimation with probiotics-based ORS supplementation alleviates heat stroke-induced multiple organ dysfunction via improving intestinal thermotolerance and modulating gut microbiota in rats - Li, Lei; Chen, Juelin; Wang, Yawei; Pei, Yankun; Ren, Lijun; Dai, Xiaoyu; Li, Jinfeng; Ma, Jun; Wang, Man; Chang, Wenjun; Chen, Jikuai; Song, Qing; et al. (Frontiers in Microbiology, 2024)
Heat stroke (HS) is a critical condition with extremely high mortality. Heat acclimation (HA) is widely recognized as the best measure to prevent and protect against HS. Preventive administration of oral rehydration salts III (ORSIII) and probiotics have been reported to sustain intestinal function in cases of HS. This study established a rat model of HA that was treated with probiotics-based ORS (ORSP) during consecutive 21-day HA training. The results showed that HA with ORSP could attenuate HS-induced hyperthermia by regulating thermoregulatory response. We also found that HA with ORSP could significantly alleviate HS-induced multiple organ injuries. The expression levels of a series of heat-shock proteins (HSPs), including HSP90, HSP70, HSP60, and HSP40, were significantly up-regulated from the HA training. The increases in intestinal fatty acid binding protein (I-FABP) and D-Lactate typically seen during HS were decreased through HA. The representative TJ proteins including ZO-1, E-cadherin, and JAM-1 were found to be significantly down-regulated by HS, but sustained following HA. The ultrastructure of TJ was examined by TEM, which confirmed its protective effect on the intestinal barrier protection following HA. We also demonstrated that HA raised the intestinal levels of beneficial bacteria Lactobacillus and lowered those of the harmful bacteria Streptococcus through 16S rRNA gene sequencing. These findings suggest that HA with ORSP was proven to improve intestinal thermotolerance and the levels of protective gut microbiota against HS.